Grammatical inference: algorithms and applications : 9th International Colloquium, ICGI 2008 Saint-Malo, France, September 22-24, 2008 : proceedings - International Colloquium on Grammatical Inference; Clark, Alexander; Coste, Francois; Miclet, L. (Laurent) (Lecture Notes in Computer Science, 2008)
This book constitutes the refereed proceedings of the 9th International Colloquium on Grammatical Inference, ICGI 2008, held in Saint-Malo, France, in September 2008. The 21 revised full papers and 8 revised short papers presented were carefully reviewed and selected from 36 submissions. The topics of the papers presented vary from theoretical results of learning algorithms to innovative applications of grammatical inference, and from learning several interesting classes of formal grammars to applications to natural language processing.